Online speaking practice: A gateway to anxiety reduction for EFL students - Aat Eska Fahmadi; Omar Mohamed Gharbi; Amr Youssef Mahmoud (Journal of Research in English Language Teaching and Linguistics, 2025)
In recent years, growing attention has been directed toward reducing anxiety in English language learning, recognizing that communicative competence is central to achieving overall proficiency. Existing research indicates that supportive learning environments, personalized feedback—especially through online platforms—and the use of digital tools such as virtual courses can help EFL students practice speaking with less pressure while improving accessibility and adaptability. Despite these advantages, there remains limited exploration of how real-time digital speaking practices specifically address speaking-related anxiety. Therefore, this study aims to examine the influence of online speaking practices on students’ anxiety levels and to evaluate the extent to which these practices effectively reduce anxiety in English language learning. This study employed a qualitative approach, and structured interviews were conducted with 19 randomly selected English as a Foreign Language (EFL) students. The results reveal that online speaking practices can significantly reduce anxiety by providing flexible, self-paced learning environments where students have greater control over their learning conditions. These online settings allow students to build confidence gradually without the immediate pressure commonly associated with face-to-face feedback or classroom interactions. Furthermore, the findings suggest that online speaking tasks encourage students to take more initiative and engage more consistently in speaking activities. Based on these insights, the study recommends adopting a balanced learning approach that integrates both online and in-person speaking opportunities. Such an approach can help manage anxiety while also strengthening students’ adaptability and communication abilities for academic, professional, and social contexts. Educators are encouraged to incorporate this blended strategy into language programs to support more comprehensive skill development.